Hydrogel Formulation of Usnic Acid and Antibacterial Activity Test Against Propionibacterium acne - Lili Fitriani; Afifah; Friardi Ismed; Amri Bakhtiar (MDPI AG, 2018)
Usnic acid is known for its remarkable antimicrobial activity. The aim of this research was to formulate hydrogel of usnic acid and evaluate the antibacterial activity against Propionibacterium acne. Due to low solubility of usnic acid, solid dispersion was prepared using PVP K-30. In this study, intact usnic acid (UA) and usnic acid-solid dispersion (UA-SD) was formulated in hydrogel using several gelling agents: Aqupec HV-505, sodium alginate and HPMC K 100M. Concentration of each gelling agent was optimized for hydrogel base. All of hydrogel base showed homogenous gel, pH at range 5.37⁻6.33 and viscosity in range 259.07⁻10,759.00 cps. Hydrogel was prepared by dispersing 1% intact UA and 3% UA-SD in three different gelling agents. The hydrogel was evaluated for pH, viscosity, stability test for two months and microbiology test. The amount of usnic acid in hydrogel was determined by spectrophotometry UV-Vis. Hydrogel UA showed non-homogenous gel, while hydrogel usnic UA-SD was homogenous. The pH of all hydrogel was in range 5.5⁻6.4 and viscosity was 2,017.03⁻3,866.52 cps. All the hydrogel was stable and diameter inhibition of hydrogel was in a range 20⁻32 mm. The amount of usnic acid in hydrogel was in range 96.9⁻99.23%. In conclusion, hydrogel UA-SD is promising preparation in handling acne.